A Literature Review on Medicinal Plants That are being Used in Traditional Medicine for the Management of the Snake Bites in Sri Lanka - Vinotha, S.; Nushrath Roshana, M. (Asian Plant Research Journal, 2018)
Background: Traditional Medicine is time-tested and still caters to the health needs of the society and provides health care through prophylactic treatment and rejuvenation. Today poisonous snake bites are life-threatening problems resulting in high morbidity and mortality all over the world including Sri Lanka. The medicinal plants available locally and used widely by traditional healers. Therefore they need attention in this aspect. Aim: The primary aim of this study was to do a literature review on essential characteristics of medicinal plants which are being used for the management of snake bites in Traditional Medicine. Place and Duration of the Study: Unit of Siddha Medicine, University of Jaffna from April to June 2018. Methodology: Data for the literature review on 94 medicinal plants from 41 families were collected from relevant books and research articles. The characteristics of the medicinal species that were identified for the review were morphology; habitat; parts used; Siddha properties such as taste, potency and efficacy; pharmacological action; the number of plants used for dietary purposes; poisonous plants; phytochemical contents and mode of transmission. Results: From the 94 medicinal plants, 9 (9.6%) of the species were found in Fabaceae and followed by 6 (6.38%) in Cucurbitaceae and Apocynaceae families. Based on the morphology 24 (25%) plants were herb and shrub; 42 (45%) were found in the natural habitat. From these plants, 31 species (26%) were used as root and 29 (24%) as leaves. These plants contain: Siddha properties such as bitter taste [52 (48.14%)]; hot potency [64 (70.32%)] and pungent efficacy [68 (72.34%)]. Pharmacological actions such as diuretic [36 (38.3%)]; tonic [35 (37.23)]; astringent [33 (35.1%)] and stimulant [32 (34.04%)]. Phytochemicals such as flavonoids 88 (93.61%) and saponin 81 (86.17%) were highly found in these medicinal plants. Fifty (53.19%) of these species were used as external and internal medication in the management of snake bites. Conclusion: This literature review provides useful documented evidence on the management of snake bites in Traditional Medicine. However, there is a need for further extensive scientific studies to be carried out to justify its clinical potential in the management of snake bites.
Keywords: Medicinal plants; Management; Snake bite; Traditional medicine